Genetic variability and correlation in garden pea (Pisum sativum sub sp Hortense) for yield and yield attributing traits - SINGH, S R; AHMED, N; RANJAN, J K; RANJAN, PRAGYA; MIR, ABID (The Indian Journal of Agricultural Sciences, 2016)
Assessment of genetic variability and relationship among important horticultural traits was done in garden pea. There was wide variability among the 32 genotypes for all traits. Little or no difference between genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV) for all traits confirmed low environmental influence on the characters under study. High PCV for pod yield (q/ha), number of pods/plant and average pod weight indicated additive gene action. High variability with high to moderate genetic advance for pod yield (q/ha), pod yield/plant, number of pods/plant, 10 pod weight, shelling percentage and plant height suggested additive gene action and ability of improvement through selection. Higher genotypic correlations revealed inherent association among traits. Strong character association of number of pods/plant with pod yield suggested it as selection criterion for high yield. Adequate genetic variability within germplasm indicates scope for genetic improvement of yield and quality traits. Pods/plant had maximum direct effect on pod yield. Conclusively, selection based on higher pods/plant, number of seeds/pod, average pod weight, pod width and plant height may improve pod yield.